Clinical significance in self-rated HRQoL among survivors after childhood cancer – demonstrated by anchor-based thresholds. (April 2014) - Jervaeus, Anna; Lampic, Claudia; Johansson, Eva; Malmros, Johan; Wettergren, Lena
Abstract Background. There is a need to establish clinically relevant thresholds (anchors) for identification of differences in health-related quality of life (HRQoL) and thereby provide stronger evidence regarding the HRQoL of childhood cancer survivors. Aim. To investigate HRQoL in childhood cancer survivors with a standardised instrument and to establish thresholds for clinically significant differences by using qualitative interviews as anchors. An additional aim was to investigate survivors' HRQoL in relation to an age-matched comparison group without cancer experience. Material and methods. Self-rated HRQoL (KIDSCREEN-27) was assessed in a national cohort of survivors (n = 63, aged 12–22) and a comparison group (n = 257, aged 11–23). Findings from qualitative interview data were also used (n = 61); three subgroups ("Feeling like anyone else"; "Feeling almost like others"; "Feeling different") were identified based on survivors own perception of influence on daily life. Effect size calculations based on means from the KIDSCREEN-27 dimensions were performed using the subgroups as anchors to indicate clinical importance. Furthermore, standard multiple regression analyses were performed. Results. Effect sizes between the subgroups "Feeling like anyone else" and "Feeling almost like others" and the group "Feeling different" were large for all dimensions (1.04–2.07). The multiple regression models showed that being a survivor was significantly associated with one of the dimensions, School Environment, where survivors scored higher HRQoL. Furthermore, female sex and older age (17–23 years) significantly contributed to lower self-rated HRQoL. Conclusion. In clinical practice the KIDSCREEN-27 could be a useful screening tool to identify survivors of childhood cancer in need of extra support, using KIDSCREEN dimension mean values of 45 or less as thresholds. Larger scale studies are recommended to identify and test thresholds with regard to different age groups and time since diagnosis.